Zakah collection and distribution framework in Federal Territory : a study on selective Islamic banking institutions - Raja Norhanani binti Raja Norabidin Shah (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Zakah is one of the pillars of Islam, and it is the financial instrument and resource of development to Muslim's economy. One of the institutions that runs business based on Shariah is Islamic Banking Institutions. The management of zakah in each state has to be in line with Shariah, and it is observed that the practice of zakah collection and distribution in Federal Territory is complied with the principle of Shariah. Through examinations on the zakah collection and distribution framework in Federal Territory, Malaysia, we can expect that the collection and distribution figures will continue to increase in subsequent years from the efforts taken by zakah institutions. Thus, this paper will review and analyze the zakah collection and distribution framework in Federal Territory, focuses on the selective Islamic Banking Institutions based on observations and come out with some recommendations for better improvement which are more suitable and can be implemented comprehensively. Comments and suggestions that have been presented are intended to create a better and high quality services for zakah institutions in order to collect and distribute zakah for Muslim community who are in need.